Exfoliation of clay layers in polypropylene matrix using potassium succinate-g-polypropylene as compatibilizer - Rama, Mallikarjuna Shroff; Neppalli, Ramesh; Chellaswamy, Ramesh; Swaminathan, Sivaram (Composites Science and Technology, 2010)
The efficiency of potassium succinate-g-polypropylene (KPPSA) as compatibilizer for the dispersion of clay in a high molecular weight polypropylene during melt mixing for the preparation of nanocomposites was evaluated and compared with maleic anhydride-g-polypropylene (PPMA). Nanocomposites were prepared by direct melt mixing and by masterbatch methods and the structure obtained was characterized by WAXD and TEM. The exfoliation and better dispersion of the organoclay was observed with KPPSA than PPMA. The dispersion of clay was found to be dependent on the method of preparation, type and the amount of compatibilizer used. The dispersion was better when the nanocomposites were prepared by two step masterbatch route than the single step direct mixing method. Flexural moduli and crystallization behavior were studied and correlated with the dispersion of organoclay in the PP matrix. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: differential scanning calorimetry; Mechanical property; Nano composites; Nanoclays; polypropylene

Role of the molecular structure of carboxylate-alumoxanes in the enhanced nucleation of polypropylene - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Chemical Communications, 2015)
We have reported the use of carboxylate-alumoxanes as efficient nucleating agents for isotactic polypropylene (iPP) with a possible structural correlation to the nucleation efficiency. The unique, butterfly-like structure of carboxylate-alumoxanes correlates well with the nucleation characteristics of iPP and, for the first time, the impact of a thermally induced, crystalline transition of carboxylate-alumoxanes, which alters neither the structural conformation nor the nucleation efficiency of the transformed material, is demonstrated.

Enhanced nucleation of polypropylene by metal-organic frameworks (MOFs) based on aluminium dicarboxylates: influence of structural features - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (RSC Advances, 2016)
Metal-organic frameworks (MOFs) based on aluminium dicarboxylates provide a new platform for the enhanced nucleation of isotactic polypropylene (iPP). For instance, aluminium dicarboxylates exhibit a unique butterfly-like structure similar to that of carboxylate-alumoxanes and correlates well with the nucleation characteristics of iPP. A subtle change in the structure of the ligand backbone (fumarate/succinate) does not alter the framework structure despite changing the hydrophilic/hydrophobic character and its subsequent nucleation characteristics. This suggests that the nucleating agent should facilitate favourable interaction with hydrophobic iPP for efficient nucleation. Further, a systematic variation of the alkyl chain length in the Al-dicarboxylate does not change the nucleation efficiency considerably, even though it increases the distance between the octahedral alumina chains in the metal-organic framework, suggesting that the butterfly-like structure present in the framework is a key aspect for nucleation. Finally, the significance of the orientational conformation of the dicarboxylate around the metal centre for the nucleation is confirmed by the poor nucleation efficiency of chromium and zirconium suberate MOFs where the orientation of suberate would be different from that of aluminium suberate due to the difference in the ligation of the carboxylate group. The present work thus provides valuable pathways for developing new nucleating agents based on MOFs with appropriate selection and orientation of the organic linkers around the metal centre.

New understanding on regulating the crystallization and morphology of the beta-polymorph of isotactic polypropylene based on carboxylate-alumoxane nucleating agents - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Macromolecules, 2016)
Carboxylate alumoxane derived from p-n-alkylbenzoic acids, where n-alkyl group changes from 2 to 8 carbon atoms, exhibits dual nucleating ability and nucleates isotactic polypropylene (iPP) into predominantly in the beta-phase under specific conditions. The selectivity of the beta-phase nucleation depends on the concentration of the nucleating agent, end melting temperature and cooling rate. The beta-phase obtained from p-n-alkylbenzoate-alumoxanes is compared with the beta-phase obtained from calcium pimelate (CaP), an efficient beta-phase selective, nucleating agent, using the results from DSC, WAXS, and SAXS analysis. The lamellar morphology of iPP nucleated with different nucleating agents crystallized at different crystallization temperatures (T-C) under controlled nonisothermal conditions are evaluated using SAXS analysis. The long period increases with increasing crystallization temperature and the long period of the beta-phase is always larger than that of the alpha-phase for a given crystallization temperature. Furthermore, the variation of long period with crystallization temperature clearly brings out two crystallization temperature ranges; the low temperature range and the high temperature range. However, the beta-phase shows a lower changeover temperature compared to that of the alpha-phase. The one-dimensional correlation analysis of the beta-phase shows that the thickness of the crystal lamellae (lc) increases with T-C and exhibits the low and high crystallization temperature ranges, while the thickness, of the amorphous layer (la) more or less remains constant. In-situ high temperature WAXS studies capture the beta-phase to the a-phase transition and the transformed material con-elates well with the lamellar thickness of the beta-phase. The morphological difference between the alpha- and the beta-phases are discussed and attributed to the differences in the impact properties and the melting temperature. This study clearly demonstrates that the lamellar morphology mainly depends on the T-C and not on the nature of the nucleating agents.

Isothermal cold crystallization kinetics of borassus powder/poly(lactic acid) biocomposites - Marathe, Yogesh Nana; Chellaswamy, Ramesh; Badiger, Manohar Virupax (Polymer Crystallization, 2020)
Poly(lactic acid) (PLA) is an important bioplastic which is semicrystalline with very slow crystallization rate. Therefore, the processed PLA products are usually amorphous and transparent with low mechanical properties. Currently, research efforts are focused on enhancing the crystallization rate of PLA. In this work, natural borassus fibers are incorporated into PLA and the isothermal cold crystallization kinetics is investigated using differential scanning calorimetry and Avrami equation. The isothermal cold crystallization studies revealed that, the relative crystallinity increases with the increasing content of borassus. The Avrami exponent “n” was determined ~2.0 indicated the one‐dimensional crystal growth with rod‐like geometry. The overall crystallization rate increased due to the borassus content and was expressed by crystallization halftime (t1/2). This study clearly showed that borassus fibers act as nucleating agent.